TRAGEDI EKSISTENSI DALAM NOVEL NOTES FROM THE UNDERGROUND KARYA FYODOR DOSTOEVSKY: KAJIAN EKSISTENSIALISME SARTRE - , DIAN EKA SARI; , Prof. Dr. C. Soebakdi Soemanto, S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This Reserch describes the tragedy of human existence in the novel entitled Notes from the underground written by Fyodor Dostoevsky, applying existentialism theory proposed by Jean-Paul Sartre. Existentialism allows this research to question about the ability of human freedom to transcend objectivity manifested through a desire to achieve an ideal existence, as well as the process of tragedy which is rooted from the freedom it self. The problem is analyzed by using the concept of individual freedom based on Jean-Paul Sartre's existentialism, that underlies human desire to achieve an ideal existence (being-in-itself-for-itself). Then, the look and bad-faith triggering the tragedy of human existence. Sartre declared the term âengangementâ to express the authors's involment as a speaker in literary works. Text is employed in discourse